Integrated Confocal and Scanning Probe Microscopy for Biomedical Research - B.J. Haupt; A.E. Pelling; M.A. Horton (The Scientific World Journal)
Atomic force microscopy (AFM) continues to be developed, not only in design, but also in application. The new focus of using AFM is changing from pure material to biomedical studies. More frequently, it is being used in combination with other optical imaging methods, such as confocal laser scanning microscopy (CLSM) and fluorescent imaging, to provide a more comprehensive understanding of biological systems. To date, AFM has been used increasingly as a precise micromanipulator, probing and altering the mechanobiological characteristics of living cells and tissues, in order to examine specific, receptor-ligand interactions, material properties, and cell behavior. In this review, we discuss the development of this new hybrid AFM, current research, and potential applications in diagnosis and the detection of disease.